2019
DOI: 10.1186/s41936-019-0091-5
|View full text |Cite
|
Sign up to set email alerts
|

Redescription of the feather mite Gabucinia delibata (Robin, 1877) (Astigmata: Gabuciniidae), newly recorded from the hooded crow, Corvus cornix (Linnaeus, 1758) (Passeriformes: Corvidae) in Egypt

Abstract: Background: Faunistic information about feather mites in Egypt is scarce, as well as in the Middle East region. Results: Gabucinia delibata (Robin, 1877) (Astigmata: Pterolichoidea: Gabuciniidae) is recorded for the first time in Egypt from the hooded crow, Corvus cornix (Linnaeus, 1758) (Passeriformes: Corvidae). Adult males and females of G. delibata are redescribed and illustrated. Examined specimens were compared with previous description and anomalous features were discussed. Conclusion: The new mite reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(7 reference statements)
1
0
0
Order By: Relevance
“…neotropica Hernandes, 2020-are associated with crows Corvidae (Passeriformes) (Mironov et al, 2014). Gabucinia delibata, has been reported so far on hosts belonging to the genera Corvus, Coloeus, and Pica across the Holarctic region (Negm and Hassan, 2019;Hernandes, 2020); in the present study, it is reported on the hooded crow, Corvus cornix, for the first time in Türkiye.…”
Section: Genus Eustathia Oudemans 1905supporting
confidence: 47%
“…neotropica Hernandes, 2020-are associated with crows Corvidae (Passeriformes) (Mironov et al, 2014). Gabucinia delibata, has been reported so far on hosts belonging to the genera Corvus, Coloeus, and Pica across the Holarctic region (Negm and Hassan, 2019;Hernandes, 2020); in the present study, it is reported on the hooded crow, Corvus cornix, for the first time in Türkiye.…”
Section: Genus Eustathia Oudemans 1905supporting
confidence: 47%